Phonological principles in intervention programmes for children with cleft lip & palate - Georgiou, Anastasios M. (My University, 2026)
Georgiou, A. M. (2012, April). Phonological principles in intervention programmes for children with cleft lip & palate. Poster session presented at the 12th Pan-Hellenic Congress of Speech & Language Therapists. Clinical Interventions in Speech & Communication Disorders. Multidisciplinary approach. Athens, Hellas.